Complicated acute appendicitis presenting as a necrotizing fasciitis of the abdominal wall: a case report - Tiryaki Baştuğ, Betül; Subaşı, Berkay; Emekli, Emre; Parpucu, Kübra; Kebapçı, Mahmut (The European Research Journal, 2018)
Acute appendicitis is one of the most common surgical diseases, but necrotizing fasciitis of the abdominal wall because of perforation is extremely rare. A 50-year-old male presented to the emergency department with severe right-sided abdominal pain for a week. He was hypothermic, hypotensive, and tachycardic. His abdomen was distended, with a large, tender, erythematous region over the right abdominal wall. Laboratory evaluation revealed leukocytosis, acute kidney injury. Computed tomography revealed large collections of fluid and gas in the right abdominal wall as well as inflammation surrounding the right colon. The patient was resuscitated with intra-venous fluid, started on broad-spectrum antibiotics, and emergently brought to the operating room. The patient underwent an exploratory laparotomy, and was found to have appendicitis, which perforated into his abdominal wall resulting in a necrotizing soft tissue infection. It is important to recognize this complication early and proceed immediately to the operating room.